Globalisation and its challenges with special reference to China - Heng, S. H. (Universiti Kebangsaan Malaysia, 2001)
The main approach of this study of globalisation is historical. We look at three periods in world history when the most promising and enduring civilisation was overtaken by the less promising one. A simple model is proposed to make sense out of the tremendous shift. Subsequently we use the findings to see if they can provide some insights into understanding the challenges posed by globalisation to the People’s Republic of China. It is suggested that the most pressing task is to strengthen the state to cope with the new challenges. State strength is not the same as authoritarianism. Concretely, the task is to nurture a stratum of senoir civil servants dedicated to the interests of the state; they must be selected on the basis of competence and integrity. They are to form the crucial instrument in political stability, social harmony and national cohesion. The on-going economic modernisation in Asia represents an opporutnity for full social development, to encompass spirituality, cultural advancement, civil society and material progress.